Cross-Tissue Characterization of Heterogeneities of Mesenchymal Stem Cells and Their Differentiation Potentials - Hou, Wenhong; Duan, Li; Huang, Changyuan; Li, Xingfu; Xu, Xiao; Qin, Pengfei; Hong, Ni; Wang, Daping; Jin, Wenfei (Frontiers in Cell and Developmental Biology, 2021)
Mesenchymal stem/stromal cells (MSCs) are promising cell source for regenerative medicine and treatment of autoimmune disorders. Comparing MSCs from different tissues at single cell level is fundamental for optimizing clinical applications. Here we analyzed single cell RNA-seq data of MSCs from 4 tissues, namely umbilical cord, bone marrow, synovial tissue and adipose tissue. We identified 3 major cell subpopulations, namely osteo-MSCs, chondro-MSCs, adipo/myo-MSCs, across all MSC samples. MSCs from the umbilical cord exhibited the highest immunosuppression, potentially indicating it is the best immune modulator for autoimmune diseases. The differentiation potentials of MSC subpopulations, which are strongly associated with their subtypes and tissue sources, showed pronounced subpopulation differences. We found MSC subpopulations expanded and differentiated when their subtypes consist with induction directions, while the other subpopulations shrank. We identified the genes and transcription factors underlying each induction at single cell level and subpopulation level, providing better targets for improving induction efficiency.